Intraspecific difference among herbivore lineages and their host‐plant specialization drive the strength of trophic cascades. (11th May 2020) - Sentis, Arnaud; Bertram, Raphaël; Dardenne, Nathalie; Simon, Jean‐Christophe; Magro, Alexandra; Pujol, Benoit; Danchin, Etienne; Hemptinne, Jean‐Louis
Abstract: Trophic cascades – the indirect effect of predators on non‐adjacent lower trophic levels – are important drivers of the structure and dynamics of ecological communities. However, the influence of intraspecific trait variation on the strength of trophic cascade remains largely unexplored, which limits our understanding of the mechanisms underlying ecological networks. Here we experimentally investigated how intraspecific difference among herbivore lineages specialized on different host plants influences trophic cascade strength in a terrestrial tri‐trophic system. We found that the occurrence and strength of the trophic cascade are strongly influenced by herbivores' lineage and host‐plant specialization but are not associated with density‐dependent effects mediated by the growth rate of herbivore populations. Our findings stress the importance of intraspecific heterogeneities and evolutionary specialization as drivers of trophic cascade strength and underline that intraspecific variation should not be overlooked to decipher the joint influence of evolutionary and ecological factors on the functioning of multi‐trophic interactions. Abstract : The influence of intraspecific trait variation and evolutionary divergence on the strength of trophic cascade remains largely unexplored. To fill this gap, we conducted an experiment to investigate how intraspecific difference among herbivore lineages specialized on different host plants influences trophic cascade strength. We provide the first evidence that the occurrence and strength of trophic cascade strongly depend on intraspecific differences among herbivores and evolutionary divergence associated with host‐plant specialization. Contrarily to theoretical expectations, cascade trophic strength was not related to density‐dependent effects mediated by herbivore population growth rate. Our findings imply that herbivore intraspecific variation and evolutionary divergence can play a stronger role in determining trophic cascade strength than density‐dependent effects.